(untitled) (diségno, 2026)
The drawings preserved in the Moretti-Magnifico Archive reveal an approach to architectural design based both on the evocation of mythical buildings and on the calculation of precise functional parameters. The three preparatory sketches for the Imperial Theatre at E42, made by Luigi Moretti in 1937 and published here, are merely rough drafts of a solution later discarded: private notes, rapid and fragmentary, yet revealing of Moretti’s method, which uses drawing as a diagram of forces to record the interweaving of structural, spatial, and perceptual tensions within which the project develops. [read more]